Parancsnoki hiba vagy katonai kényszer? : az Osztrák-Magyar Monarchia Szerbia elleni, 1914. évi hadjárata kudarcainak kérdései - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2015)
The military forces of the Austro–Hungarian Monarchy suffered heavy defeats at the beginning of the Great War as the two small Balkan states of Serbia and Montenegro successfully withstood Austro-Hungarian attacks. Some literature on military history and public historiography has held General Oskar Potiorek, the Monarchy’s commander at the seat of war responsible for the military failures. However, immediately after the war had ended, contemporary military figures stated that the problem was not due merely to a general’s incompetence. Potiorek was one of the most experienced generals of the Monarchy. The real cause of the failures lies in the events that happened in the Russian theater of war. The invasion by greater-than-expected Russian forces into the territory of the Monarchy made it necessary to redeploy to the north most of the troops fighting in the Balkans. This resulted in a special operational situation, in which Potiorek had to attack even with this unfavorable balance of forces. Even though these attempts seemed pointless, they prepared the way for the later success of the Central Powers in the Balkans. At the same time, geographical circumstances also had a great impact on the events of the Balkan theater of war. Due to the Monarchy’s transportation network, as well as to the terrain and hydrogeology in Bosnia-Hercegovina and Serbia the first offensive operations had to start from an unfavorable position. As Potiorek had to keep the events of the Russian theater in mind, and as the takeover of Serbia and Montenegro was an issue of the great powers and military politics, the contrast between political and military expectations and goals became so extreme as to prove unresolvable in 1914. The result of the above-mentioned factors became the first military failure of the Austro–Hungarian Monarchy against Serbia.